Developing Fine Motor Skills in Early Childhood through Plasticine Media - Ilham Kamaruddin; Wahid Dalail; Devin Mahendika; Ali Sibro Mulisi; Ervan; Muhammad Rif'at (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2023)
Along with the development of science and technology, there are various kinds of learning media that can be used to develop students' fine motor skills, one of which is plasticine media. The use of this media must be supported by an action in a classroom study. This research is a Classroom Action Research with descriptive qualitative research type. The formulation of the problem discusses whether the use of plasticine media can develop fine motor skills of Early Childhood at Mutiara Insani Kindergarten Bandar Lampung. The data collection techniques that researchers use are the observation method as the main method, the documentation method as a support in research and the interview method to find out the extent of the teacher's response to the application of the storytelling method in improving children's morale. The results of this study showed an increase in children's language skills in cycle I by 60% and in cycle II by 85%. Based on these results, the author can conclude that the use of plasticine media can develop children's fine motor skills at Mutiara Insani Kindergarten Bandar Lampung. The results can be seen from the development of students where in the pre-research cycle it is known that students who reach the assessment standards develop very well there are only 8 children out of all 20 students. Then in cycle I, children who have very good fine motor skills increase to 12 children and in cycle II increase again to 17 students or 85% of students have reached the predetermined assessment standards.